2003
DOI: 10.1038/sj.ejcn.1601744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foot-to-foot bioelectrical impedance analysis for the prediction of total body water in oncology outpatients receiving radiotherapy

Abstract: Objective: To investigate the accuracy of total body water (TBW) predicted by foot-to-foot bioelectrical impedance compared with a deuterium oxide dilution technique in oncology outpatients receiving radiotherapy. Design: Cross-sectional design. Setting: Two private Australian radiation oncology facilities. Subjects: In all, 27 subjects (23 males; four females); mean age 62 (715) y; mean BMI 26.2 kg/m 2 (73.6). Intervention: TBW was measured using a deuterium oxide dilution technique and predicted using foot-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 35 publications
(43 reference statements)
0
32
2
Order By: Relevance
“…In this study the best combination of low bias and narrow limits of agreement was observed in the prediction of REE from the Wang equation based on FFM. Measurement of FFM using the deuterium dilution technique is impractical in the clinical setting, and other methods such as bioelectrical impedance analysis have been shown to be inaccurate at prediction of FFM at the individual level in patients with cancer [38]. Therefore, most clinicians rely on REE prediction equations that incorporate easily measurable variables, such as body weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the best combination of low bias and narrow limits of agreement was observed in the prediction of REE from the Wang equation based on FFM. Measurement of FFM using the deuterium dilution technique is impractical in the clinical setting, and other methods such as bioelectrical impedance analysis have been shown to be inaccurate at prediction of FFM at the individual level in patients with cancer [38]. Therefore, most clinicians rely on REE prediction equations that incorporate easily measurable variables, such as body weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that footto-foot BIA is acceptable at the group level in measuring total body water and, hence FFM, in oncology patients receiving radiotherapy (Isenring et al, 2004).…”
Section: Data Collectionmentioning
confidence: 99%
“…Reactance is the resistive effect produced by the tissue interfaces and cell membranes 25 . Thanks to its potential to detect changes in tissue electrical properties, pa has been found to be an indicator for cell membrane integrity, distribution of water between the intracellular and extracellular spaces, and prediction of body cell mass in various disease conditions [26][27][28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%